The Role of Principal in Improving PAI Learning in The Corona Pandemic Period in RA TAAM Adinda Care to Overcome Gresik - Syaikhon , Muhammad; Saleh , Nanang Rokhman; Ulum , Bahrul (LPPPM STAI Darul Hikmah Bangkalan, 2021)
This research is a type of field research with a qualitative descriptive approach with the title Role of the Principal in Improving PAI Learning during the Corona Pandemic at RA Taam Adinda Kepatihan Menganti Gresik. This study aims to determine the role and strategy of school principals in improving PAI learning during the corona pandemic at RA TAAM Adinda Kepatihan Gresik. The subjects in this study were educators, students, parents, and related parties. The data collection techniques used were observation, in-depth interviews, and documentation. Data analysis was carried out using data reduction, data presentation, and drawing conclusions or verification. The results of the findings of this study can be concluded that the role of the RA Taam Adinda principal in improving Islamic Education learning during the corona pandemic in Kepatihan Menganti Gresik village was as educator, manager, administrator, supervisor, leader, innovator, and motivator that had been implemented properly and by defined goals and plans. The strategies used by the school principal in improving PAI learning during the corona pandemic at RA Taam Adinda Kepatihan Menganti Gresik were improving teaching skills for teachers, optimizing the use of media and educational facilities, carrying out regular supervision, and establishing good cooperation with the community